101 Foot Care Tips for People with Diabetes - Ahroni, Jessie H. (New Delhi Viva Books, 2010)
For people with diabetes, developing complications of the feet are a constant threat. You will find answers to the most common questions about foot care, including how to prevent and treat minor problems such as calluses, blisters, and fungal infections; and major complications such as ulcers and neuropathy.
Include Illustrations and Index
Keywords: Diabetes--Complications -- Diabetics--Health and hygiene